1977
DOI: 10.1259/0007-1285-50-594-412
|View full text |Cite
|
Sign up to set email alerts
|

The radiology of nasal injuries: problems of interpretation and clinical relevance

Abstract: Films of 50 normal patients and 50 dry skulls were examined to detect lines which might stimulate a nasal fracture. These were visible on the occipito-mental view but on the lateral view any line which reaches the anterior cortex must be regarded as a fracture. The results of an analysis of 100 patients with trauma to the nasal bone are also presented. It is concluded that radiography of the nasal bone is an unnecessary examination unless requested by the E.N.T. surgeon, and this will in any case occur infrequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Many diagnostic methods, including clinical examination (crepitus, grossly apparent deviation of the nasal bones, swelling over the nasal bridge, and periorbital ecchymosis), conventional radiography, CT, and US, have been used to evaluate nasal trauma [13]. Although a physical examination is regarded as the gold standard for diagnosis, adequate imaging is often required to address legal implications [13,15]. Furthermore, physical examination cannot determine fracture complexity [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many diagnostic methods, including clinical examination (crepitus, grossly apparent deviation of the nasal bones, swelling over the nasal bridge, and periorbital ecchymosis), conventional radiography, CT, and US, have been used to evaluate nasal trauma [13]. Although a physical examination is regarded as the gold standard for diagnosis, adequate imaging is often required to address legal implications [13,15]. Furthermore, physical examination cannot determine fracture complexity [10].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, the standard imaging modality and the initial diagnostic step were considered to be conventional radiography. However, unlike injuries on the midline of nasal bone, it is difficult to evaluate lateral nasal wall injuries on conventional radiographs [1,15,16]. Furthermore, several studies have demonstrated that conventional radiography cannot be used routinely to evaluate nasal bone fractures [1,10,17].…”
Section: Discussionmentioning
confidence: 99%
“…1 The predictive value of periosteal thickness in estimating the time of nasal trauma [8]. Midline nasal suture, nasomaxillary suture, developmental defects or thinning of the nasal wall and short radiolucent lines reaching the anterior aspect of the nasal bone may erroneously be reported as fracture lines [9]. To date, only a few studies have been conducted to assess the diagnostic value of ultrasonography in nasal bone fracture.…”
Section: Discussionmentioning
confidence: 99%
“…De Lacey and co-workers [23] concluded from a study of 100 patients with nasal bone trauma that it is an unnecessary procedure and should be carried out only upon specific request by an ENT surgeon.…”
Section: Nasal Fracturesmentioning
confidence: 99%
“…Magnetic resonance imaging is helpful in evaluating carotid-cavernous sinus fistulas (Figs. 23,24,25) [39].…”
Section: Complex Facial Featuresmentioning
confidence: 99%